2020
DOI: 10.1177/0022002720907675
|View full text |Cite
|
Sign up to set email alerts
|

Comfortably Numb: Effects of Prolonged Media Coverage

Abstract: Exposure to a single report about terrorism in the mass media can trigger a range of emotional and political reactions. The consequences of exposure to several terrorism reports in row, however, are a matter of controversy. We examine the effects of prolonged terrorism coverage using an experimental design that combines self-report measures of emotions and political attitudes with instantaneous biometric data on emotions. Consistent with research on nonassociational learning, we find that exposure to multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 88 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…The idea that people experience less-intense affective reactions to stimuli and events after an initial exposure—that is, desensitization (Campbell et al, 2014)—has received wide support. In the lab, people express less-extreme evaluations of the same affect-arousing stimulus after an initial encounter with it (Leventhal et al, 2007), and they display less-angry facial expressions in response to a first video clip depicting a terrorist attack than to a fifth clip depicting a different terrorist attack (Hoffman & Kaire, 2020). Outside the lab, people appear to become desensitized to violence after repeated exposure to it in the media (Carnagey et al, 2007; Funk et al, 2003), and clinicians leverage insights about desensitization to treat phobias and trauma (Rothbaum & Schwartz, 2002; Wolpe, 1961).…”
Section: The Present Researchmentioning
confidence: 99%
“…The idea that people experience less-intense affective reactions to stimuli and events after an initial exposure—that is, desensitization (Campbell et al, 2014)—has received wide support. In the lab, people express less-extreme evaluations of the same affect-arousing stimulus after an initial encounter with it (Leventhal et al, 2007), and they display less-angry facial expressions in response to a first video clip depicting a terrorist attack than to a fifth clip depicting a different terrorist attack (Hoffman & Kaire, 2020). Outside the lab, people appear to become desensitized to violence after repeated exposure to it in the media (Carnagey et al, 2007; Funk et al, 2003), and clinicians leverage insights about desensitization to treat phobias and trauma (Rothbaum & Schwartz, 2002; Wolpe, 1961).…”
Section: The Present Researchmentioning
confidence: 99%
“…Research in conflict studies has found that exposure to an isolated media story about terrorism causes heightened anxiety (Breckenridge, Zimbardo, and Sweeton, 2010) and support for security measures at the expensive of civil freedoms (Merolla and Zechmeister, 2009). However, Hoffman and Kaire (2020) show that prolonged exposure to several terrorism reports attenuates these effects as people quickly become habituated to hearing about political violence. Relatedly, a lengthy literature speaks to the desensitizing effects of prolonged exposure to violent crime (Fowler et al, 2009).…”
Section: Problems and Attention In Policymakingmentioning
confidence: 99%
“…This is an ordinal within-subject variable with three levels: pre-treatment, posttreatment, and follow-up (11 months after the completion of the pilot study). Including this variable aims to assess the stability of the effect of the designed program once the initial momentum of the treated topics fades from participants' recent memory, thus avoiding confusion between the effects caused by the intervention and those caused by experimental maturation, as reported in numerous similar previous studies [73,74].…”
Section: Within-subject Intervening Variable: Evolution Over Timementioning
confidence: 99%